Thirty-Day and One-Year Outcomes of Endovascular Treatments for Severe Atherosclerotic Stenosis of Intracranial ICA: Results From a Single Center - Shen, Shengli; Wang, Yingjin; He, Xudong; Ma, Ning; Gao, Feng; Song, Ligang; Sun, Xuan; Liu, Lian; Miao, Zhongrong; Duan, Hongzhou; Mo, Dapeng (Frontiers in Neurology, 2021)
Background: Endovascular treatment for intracranial atherosclerotic stenosis (ICAS) has been developed. However, the intracranial internal carotid artery (ICA) presents a particular challenge due to the location and tortuous route, and the outcomes of endovascular treatment in patients with stenosis of the intracranial ICA still have not been reported. This article retrospectively investigated the 30-day and 1-year outcomes of tailored endovascular treatment for patients with severe intracranial ICA stenosis from a single center. Methods: Between June 2014 and December 2017, 96 consecutive patients with severe atherosclerotic stenosis (70–99%) of the intracranial ICA were managed with endovascular treatment in Beijing Tiantan Hospital. Three different kinds of treatments [angioplasty with balloon dilatation alone (BD group), balloon-mounted stent (BMS group), and self-expanding stent (SES group)] were performed according to the characteristics of the lesions. The primary endpoints included any stroke or death within 30 days and ipsilateral ischemic stroke afterwards within 1 year. Secondary endpoints included the revascularization success rate (residual stenosis <30%) and the restenosis rate (stenosis ≥ 50%) within 1 year. Results: The 30-day death rate was 0, and the stroke rate of all patients was 7.3% (7/96). The stroke rate was higher in the BD group (15.8%) and SES group (9.8%) than in the BMS group (0%) (p = 0.047). Thirteen (13.5%) patients suffered at least one onset of ischemic stroke in the ipsilateral ICA territory within 1 year, and there was no significant difference among the three groups (p = 0.165). The overall revascularization success rate was 93.8%, and the revascularization success rate was significantly higher in the SES group (100%) than in the BD group (78.9%) (p = 0.006). The restenosis rate of all patients within 12 months was 20.8%, and there was no significant difference among the three groups. Patients with Mori type C target lesions were more likely to suffer stroke within 30 days (25%) and restenosis within 1 year (31.3%). Conclusions: Both the 30-day and 1-year outcomes of tailored endovascular treatments seemed to be acceptable in the treatment of symptomatic atherosclerotic stenosis of the intracranial ICA. However, this needs to be confirmed by further investigation, preferably in large multicenter randomized controlled clinical trials.